EXPERTS' OPINIONS ON THE ORGANIZATION OF UNIVERSITY PHYSICAL EDUCATION - Sakizlian M. C. (ALTIUS ACADEMY Foundation - Faculty of Physical Education and Sports, 2013)
Study on "expert opinions on the organization of university physical education" is part of a wider research aimed at optimization of physical education female students by application specific means aerobic gymnastics in physical education classes to increase their level of functional training. The experiment developed during an academic year was the comparative analysis of the experimental group, which conducted aerobics classes and control group, which participated in general physical education classes. Information taken and processed facilitated research in all its stages (preparatory phase, the basic experiment and interpretation of data obtained). Based on the received answers, was developed the strategy research of potential somatic, motor and functional female students participating in the experiment which aimed to optimize their functional training. The important scientific problem in investigational functional training is to increase efficiency by optimizing the efforts of female students training in aerobic gymnastics means. Conclusions following responses from experts in the field have shown that there is low level physical education and lack of academic research on functional training students.